2017
DOI: 10.1002/acm2.12216
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal sparing approach in fractionated stereotactic brain VMAT radio therapy: A retrospective feasibility analysis

Abstract: Volumetric Modulated Arc Therapy (VMAT) techniques for fractioned stereotactic brain radiotherapy (FSBRT) can achieve highly conformal dose distribution to intracranial lesions. However, they can potentially increase the dose to hippocampus (H) causing neurocognitive toxicity during the first four months after irradiation. The purpose of this study was to assess the feasibility of hippocampal‐sparing (HS) treatment plans in 22 patients with brain metastasis treated with VMAT technique. Firstly, we retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The proposed doses refer to conventional radiotherapy in which the fractional dose oscillates between 2 and 3 Gy. The problem arises in the case of hypofractionated RT and in particular stereotactic RT, although there are newer reports of "protective" doses in the hippocampus region in such cases [59,60].…”
Section: Clinical Situations In Which Hippocampal Protection Should Bmentioning
confidence: 99%
“…The proposed doses refer to conventional radiotherapy in which the fractional dose oscillates between 2 and 3 Gy. The problem arises in the case of hypofractionated RT and in particular stereotactic RT, although there are newer reports of "protective" doses in the hippocampus region in such cases [59,60].…”
Section: Clinical Situations In Which Hippocampal Protection Should Bmentioning
confidence: 99%
“…However, many challenges still limit the precise implementation of hippocampus‐sparing WBRT. During WBRT, cranial irradiation may induce hippocampal neural stem‐cell injury 6 . Studies have shown the correlation between memory loss or cognitive impairment and hippocampal injury 7–9 .…”
Section: Introductionmentioning
confidence: 99%